A new genus and species of Plumariidae (Hymenoptera, Chrysidoidea) from western xeric Argentina - Diez, Patricia; Fidalgo, Patricio; Roig-Alsina, Arturo (Zootaxa, 2007)
Mapluroides ogloblini, a new genus and species from the provinces of San Juan and La Rioja in western Argentina, are described. Descriptions, drawings and a discussion of its relationships to other genera of plumariids are provided. The new taxon is closely related to Plumaroides Brothers and Maplurius Roig-Alsina.